Isomeria: A discovery by Jacob Berzelius under the eye of Larry Laudan - Borges, Patricia Bisso Paz (2021)
In this work, we sought to bring Larry Laudan's epistemology, which presupposes that scientific progress is based on Problem Solving, closer to the subject of Isomerism, a research carried out by Jacob Berzelius. This theme is relevant in the study of Organic Chemistry, as isomerism is a common phenomenon and portrays the diversity of organic molecules that have the same molecular formula, but different structural properties and characteristics. However, its teaching in the classroom has been occurring in a fragmented way due to the difficulty found by teachers and students in developing the necessary abstraction to understand its most diverse representations. This work aims from the understanding of the importance and effectiveness of the discovery made by Berzelius, related to Larry Laudan's epistemology, to provide that the subject Isomerism can be approached in the classroom in a more understandable way, seeking, in this way, to minimize the difficulties between teaching and learning.